Sub-types of safety behaviours and their effects on social anxiety disorder - Gray, Emily (PLoS One, 2019)
Cognitive models suggest that social anxiety disorder (SAD) is maintained through the use of safety behaviours. Previous reports propose that these safety behaviours can be subdivided into two main categories: avoidance and impression management. Study 1 investigates whether certain safety behaviours are specific to SAD. The social behaviour questionnaire was administered to individuals with SAD (N = 106), post-traumatic stress disorder (N = 28) and non-patient controls (N = 59). A factor analysis (N = 164) replicated the previously reported avoidance and impression management subtypes. Scores for both subtypes were significantly higher in individuals with SAD than in individuals with post-traumatic stress disorder or non-patient controls. Study 2 investigated the causal role of such safety behaviours using an experimental design in a non-clinical population (N = 96). Pairs of participants each engaged in two conversations. In one of the conversations, a randomly selected participant performed either avoidance or impression management safety behaviours. In the other conversation, neither participant was instructed to use safety behaviours. Each participant rated their own anxiety and performance as well as rating the other person. Videos of the conversations were also rated. Both types of safety behaviour increased anxiety in the person performing the safety behaviour. The avoidance subtype also had broader effects on the other person that were largely absent from the impression management subtype. Taken together the studies provide support for the distinction between safety behaviour subtypes and have implications for the treatment of SAD.